Odpowiedź :
Odpowiedź:
4K - 8 K = 2
4 * 2 - 8 = 8 -8 = 0
2/ 3B - 2 B = 3
2/ 3*3 - 2 = 2/ 9 - 2 = 2/7 (chodzi o ułamek w wyniku)
t(t + 2) T = 5
5(5+2) = 5*7 = 35
2X + X^2 X = 4
2*4 + 4^2 = 8 + 16 = 24
2(4P + 1) - 5 P = -1
2(4*- 1) -5 = 2(-4) -5 = -8 -5 = -13
3M - 1 M = 4
3*4 - 1 = 12 - 1 = 11
Y(Y + 3) Y = -4
-4(-4 + 3) = -4(-1) = 4
3X^2 + 2X X = -1
3*-1^2 + 2*-1 = 3*-1 + 2*-1 = -3 -2 = -5
3,5X + 5Y X= -5 Y = 2
3,5*-5 + 5*2 = -17,5 + 10 = -7,5
MAM NADZIEJĘ ŻE POMOGŁAM
w załączniku:
:)))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))